A review on informed search algorithms for video games pathfinding - Kapi, Azyan Yusra (World Academy of Research in Science and Engineering, 2020)
Pathfinding is a broadly applied algorithm that involved the discovery of routes between two positions by avoiding obstacles at the same time. Recently, a significant number of researchers focusing on informed search algorithms for pathfinding concerning games. However, review regarding the latest optimization in the pathfinding algorithm and its advantages still lacks in the literature. To organize this heterogeneity, this paper presents a review that focused on numerous modifications to enhance the execution of the informed search algorithm through four classified perspectives: i) modification to the graph representation, ii) enhancement of heuristic function, iii) hybrid search algorithm, and iv) new data structure. This paper also aims to discuss common challenges faced by pathfinding in video games and providing future trends for optimization. While incorporating pathfinding optimization over the past decade, this paper also aims to assist new researchers by emphasizing the potential path for further exploration.